2007
DOI: 10.2527/jas.2006-239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, sex, and halothane genotype on fatty acid composition of pork longissimus muscle1

Abstract: The objective of this study was to estimate the effects of breed, sex, and halothane genotype on fatty acid composition and several fatty acid indices of lipid extracted from porcine LM. Purebred Yorkshire (n = 436), Duroc (n = 353), Hampshire (n = 218), Spotted (n = 187), Chester White (n = 173), Poland China (n = 124), Berkshire (n = 256), and Landrace (n = 187) pigs (n = 1,934; 1,128 barrows and 806 gilts) from 1991, 1992, 1994, and 2001 National Barrow Show Sire Progeny Tests were used. Pigs were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
61
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 37 publications
(46 reference statements)
18
61
4
Order By: Relevance
“…For instance, it is known that inclusion of linseed in diets for pigs (Corino et al, 2008) and sheep (Niedźwiedzka et al, 2008) improves the fatty acid profile of their tissues. It is also known that gender and castration, as well as weight at slaughter influence the fatty acid profile in pig tissues (Zhang et al, 2007;Peinado et al, 2012). On the other hand, studies on the genetic variability of fatty acid profiles in tissues of livestock, including the pig, are quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is known that inclusion of linseed in diets for pigs (Corino et al, 2008) and sheep (Niedźwiedzka et al, 2008) improves the fatty acid profile of their tissues. It is also known that gender and castration, as well as weight at slaughter influence the fatty acid profile in pig tissues (Zhang et al, 2007;Peinado et al, 2012). On the other hand, studies on the genetic variability of fatty acid profiles in tissues of livestock, including the pig, are quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of available literature reporting relationship between pH and fatty acid composition, but a number of genetic studies showed that pigs susceptible to low ultimate pH showed a similar proportion of fatty acid composition with our current data. Zhang et al (2007) reported that pigs with NN genotype (normal) had more C16:0 and C18:1 and less C18:2 and C20:4 than Nn pigs. Furthermore, RN¯ carrier gilts had the lowest amount of saturated fatty acid and MUFA, but had the highest amount of PUFA (Lundström et al, 1998).…”
Section: Sensory Characteristics and Fatty Acid Compositionmentioning
confidence: 99%
“…Furthermore, ultimate pH of pork muscle is the most important single attribute influencing both eating quality (Lindahl et al, 2006; Huff-Lonergan and Lonergan, 2005) and fatty acid composition in particular genotype of pigs (Lundström et al, 1998;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Duroc pigs are characterised by low frequency of that gene (Houde et al 1993;Dovč et al 1996;Urban et al 2002;Zhang et al 2007).…”
mentioning
confidence: 99%